Mnożenie jednomianów przez sumy algebraiczne...
a) 2a(b-3)-2b(a-3)
b) a(a+b)+a(a-b)+b(b+a)+b(b-a)
c) 5a(a-2)+2a(a+5)
d) 3(a+2b-3c)-2(a-2c)+5(c-b)-(a+b)
e) 8x(x+y)-2y(y-x)+1/2(6x do potęgi 2 + 8x do potęgi 2)-2(y do potęgi 2 + 5xy)
f) 1/2a(a+1)-2(a do potęgi 2 podzielić przez 4 - a/2
g) 1/3a(a+1)-4(1/3a do potęgi 2 - 1/12a)-a(1-a)
h) 0,2(5a+10b)-7(0,1a-b)+a-b

1

Odpowiedzi

2010-01-20T14:24:40+01:00
A) 2a(b-3)-2b(a-3) = 2ab - 6a - 2ab + 6b = 0
b) a(a+b)+a(a-b)+b(b+a)+b(b-a)= a² + ab + a² - ab + b² + ab + b² - ab = 2a² + 2b² = 2(a² + b²)
c) 5a(a-2)+2a(a+5)= 5a² - 10a + 2a² + 10a = 3a²
d) 3(a+2b-3c)-2(a-2c)+5(c-b)-(a+b)= 3a + 6b - 9c - 2a + 4c + 5c - 5b - a - b = 0
e) 8x(x+y)-2y(y-x)+1/2(6x² + 8x²)-2(y² + 5xy)= 8x² + 8xy - 2y² + 2xy + 3x² + 4x² - 2y² - 10xy = 15x² - 4y²
f) 1/2a(a+1)-2(a² podzielić przez 4 - a/2= 1,/a² + 1/2a - 2a²/4 + 2a/2 = 2a² + 2a - 2a² + 2a = 4a
g) 1/3a(a+1)-4(1/3a² - 1/12a)-a(1-a)= 1/3a² + 1/3a - 4/3a² + 1/3a - a + a² = - 1/3 a
h) 0,2(5a+10b)-7(0,1a-b)+a-b = a + 2b - 0,7a + 7b + a - b = 1,3a + 8b
1 4 1